2020
DOI: 10.15562/phpma.v8i1.248
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body image and tea drinking habits with anemia among adolescent girls in Badung District, Bali, Indonesia

Abstract: Background and purpose: The prevalence of anemia among adolescent girls in Indonesia remains high. Poor nutrition is a risk factor of anemia among adolescent girls, which is likely related to food intake restrictions to achieve a desired body shape (body image), and the habit of drinking tea while eating which can affect the absorption of iron. This study aims to determine the relationship between anemia with body image perception and tea drinking habits among adolescent girls.Methods: This study used a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…Based on this, it is in line with research conducted by 17 who states that there is a significant relationship between body image and nutritional status in adolescents, so adolescents are susceptible to iron deficiency anemia. This is in line with the research 18 that states that 32% of perceptions of negative body image can increase anemia in young women aged 15-18 years because body image affects nutritional status in adolescents 19 . Adolescent eating habits, including nutritional status, significantly impact health.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on this, it is in line with research conducted by 17 who states that there is a significant relationship between body image and nutritional status in adolescents, so adolescents are susceptible to iron deficiency anemia. This is in line with the research 18 that states that 32% of perceptions of negative body image can increase anemia in young women aged 15-18 years because body image affects nutritional status in adolescents 19 . Adolescent eating habits, including nutritional status, significantly impact health.…”
Section: Introductionsupporting
confidence: 91%
“…This is in line with research conducted by 33 the results (ρ=<0.05) showed that nutrition education interventions could increase knowledge, attitudes, and health practices about anemia in adolescents. Lack of knowledge of, history of not consuming iron supplements can increase the risk of anaemia so this needs to be considered in developing policies to reduce the incidence of anaemia in young women 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian lainnya menunjukkan remaja putri dengan pola minum teh selama makan berisiko 52 kali lebih tinggi mengalami anemia (Putra et al, 2020). Kecukupan zat besi remaja putri ditentukan oleh penyerapan zat besi.…”
Section: Hubungan Kejadian Anemia Denganunclassified